Thermal analysis of thermo-electric generator systems in hybrid electric vehicles under different operating conditions - Khoshnevisan, Alireza; Changizian, Sina; Raeesi, Mehrdad; Ahmadi, Pouria; Javani, Nader (SPRINGER, 2023)
Thermoelectric generators have emerged as a potential method for recovering energy from vehicle exhaust. In this study, a hybrid electric vehicle with a thermoelectric generator is dynamically designed and modeled in Simcenter Amesim software. The comprehensive model of the hybrid vehicle system that has been modeled can navigate in all-electric and parallel hybrid modes according to its control method. The driving cycle measured in Tehran city is used in this study, and its results were compared to the other standard driving cycles. In order to analyze the vehicle's dynamic behavior under varied driving situations, two overall scenarios, including constant and changing velocities, were studied. Seven speed profiles were considered in the constant speed mode, and their effects on the amount of energy produced by the thermoelectric generator were shown. It was discovered that with a constant speed of 40 m s(-1), the energy production due to temperature difference in the TEG modulus is 96.9 kJ, whereas this amount was 42.8 kJ in the real driving condition. Also, it was demonstrated that increasing vehicle's velocity raises the flow rate and temperature of exhaust gases, enhancing the effect of the thermoelectric generator. In addition, the performance of thermoelectric generators' energy production in standard cycles compared to the surveyed cycle of Tehran city has been investigated. It was observed that the amount of energy ratio, which was 6% in the real driving cycle, could reach 13% in the standard driving cycle.
Keywords: Thermoelectric generators; Hybrid electric vehicle; Waste heat recovery; Dynamic modeling; ENERGY RECOVERY; OPTIMIZATION; EXHAUST; PERFORMANCE; TRENDS; Thermodynamics; Chemistry